ORGANIC AGRICULTURE IN THE LEGAL FRAMEWORK OF THE REPUBLIC OF KAZAKHSTAN AND PEOPLE’S REPUBLIC OF CHINA: REGULATION, STANDARDS AND BARRIERS - Dalin, Wang; Nyssanbekova , Lyazzat Begimzhanovna (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
This article presents a comprehensive comparative-legal analysis of the regulation of organic agriculture in the Republic of Kazakhstan and the People’s Republic of China within the context of global demand for sustainable production and environmentally safe food systems. The study focuses on a comparative analysis of legal norms governing the certification, standardization, and export of organic products in these countries, as well as identifying institutional and procedural barriers hindering effective bilateral trade. Particular attention is paid to identifying institutional and regulatory barriers impeding bilateral trade in organic products between the RK and China. The authors examine the dynamics of the organic sector’s development in Kazakhstan, including state support measures, legislative initiatives, and the growth of certified farming systems. It is revealed that while internal regulation is actively progressing, Kazakhstan faces challenges in adapting to international standards (Codex Alimentarius, IFOAM) and China’s strict certification requirements (COPC). The analysis shows that despite advancements in legal framework development, Kazakhstan encounters obstacles, including the need to align with international standards and Chinese certification norms, which are often more rigorous. China’s legislation is analyzed as a highly standardized and digitized system ensuring strict control over the domestic market and import of organic products. Using a comparative approach, the study assesses the specifics of foreign economic operations, the impact of subsidies, the role of national standards, and institutional support. The conclusion formulates practical recommendations for harmonizing legal approaches and eliminating barriers to organic product trade between the two countries.